Cultures of correspondence in early modern Britain - Daybell, James (Material texts., 2016)
In Cultures of Correspondence in Early Modern Britain leading scholars approach the letter from different disciplinary perspectives to illuminate its workings. Contributors to this volume examine how elements, such as handwriting, seals, ink, and use of space, were vitally significant to how letters communicated.